EFEKTIVITAS MANAJEMEN HUBUNGAN MASYARAKAT DI WILAYAH HUTAN TROPIS LEMBAB : STUDI KASUS PERENCANAAN HINGGA EVALUASI BERKELANJUTAN - Shofiyyah, Alya; Kristianti , Diyah Ayu; Lu Gede, Ni; Warman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research proves the effectiveness of community relations management in humid tropical forests, with a focus on planning, implementation and evaluation processes. This research identifies key challenges and assesses the impact of current practices on ecology and community well-being. This study provides recommendations to improve management strategies, promote sustainable forest conservation, and improve outcomes for local communities. This type of research is qualitative with library study data collection techniques. Based on research, it is known that the effectiveness of Community Relations management in humid tropical forest areas depends on a comprehensive approach that includes careful planning and ongoing evaluation. By combining community-based strategies, capacity building, and a harmonious blend of traditional and modern communication methods, Community Relations efforts can resonate deeply with local communities while addressing environmental and social challenges. Collaborative partnerships between multiple stakeholders, coupled with a commitment to transparency, accountability and long-term engagement, are critical in fostering trust and ensuring Public Relations campaigns are sustainable and impactful. Sustainability evaluation not only ensures the adaptability and relevance of these efforts, but also strengthens the alignment of these efforts with the needs of communities and the evolving ecosystems they seek to support, thereby making Community Relations management an important tool for sustainable development in critical areas This.